2015
DOI: 10.4103/0972-3919.152946
|View full text |Cite
|
Sign up to set email alerts
|

18-F flourodeoxy glucose positron emission tomography-computed tomography imaging: A viable alternative to three phase bone scan in evaluating diabetic foot complications?

Abstract: Background:This paper is based on the initial findings from a prospective ongoing study to evaluate the efficacy of flourodeoxy glucose positron emission tomography-computed tomography (FDG-PET CT) in diabetic foot evaluation.Objective:The aim was to compare the diagnostic accuracies of three phase bone scan (TPBS) and FDG PET-CT (FDG-PET) in diabetic foot evaluation.Methods:Seventy-nine patients with complicated diabetic foot (osteomyelitis/cellulitis, Charcot's neuropathy) were prospectively investigated. TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…While the pooled sensitivity of all the different imaging modalities were comparable (89‐93%), the specificity of MRI (75%, 63‐84%) and 111 In‐oxine WBC scintigraphy (75%, 66‐82%) were considerably lower than 99m Tc‐HMPAO WBC scintigraphy (92%, 78‐98%) and 18 F‐FDG‐PET/CT (92%, 85‐96). Five studies identified in our search were included in this meta‐analysis. We found one small, prospective preliminary study that was not included in the meta‐analysis that reported similar results for 99m Tc‐HMPAO WBC imaging in diagnosing diabetic foot osteomyelitis (sensitivity 90% and specificity 86%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While the pooled sensitivity of all the different imaging modalities were comparable (89‐93%), the specificity of MRI (75%, 63‐84%) and 111 In‐oxine WBC scintigraphy (75%, 66‐82%) were considerably lower than 99m Tc‐HMPAO WBC scintigraphy (92%, 78‐98%) and 18 F‐FDG‐PET/CT (92%, 85‐96). Five studies identified in our search were included in this meta‐analysis. We found one small, prospective preliminary study that was not included in the meta‐analysis that reported similar results for 99m Tc‐HMPAO WBC imaging in diagnosing diabetic foot osteomyelitis (sensitivity 90% and specificity 86%).…”
Section: Resultsmentioning
confidence: 99%
“…References: Lauri et al, Ertugrul et al, Johnson et al, Nawaz et al, Newman et als, Shagos et al, Blume et al, Treglia et al, Rastogi et al, Abdel Razek and Samir, Aslangul et al, and Poirier et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shagos et al (51) reported that 18 F-FDG PET was more specific than bone scintigraphy for osteomyelitis, whereas bone scintigraphy was more sensitive than 18 F-FDG PET for the neuropathic joint. Schwegler et al (52).…”
Section: Diabetic Pedal Osteomyelitismentioning
confidence: 99%